RETRACTED: Morphological characteristics, humus and nutrient content of recent and buried soils of the Inozemtsevo mound - Al-Darraji M.M.; Tshovrebov V.S. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001